Responding to the Needs of the Homeless in the COVID-19 Pandemic: A Review of Initiatives in 20 Major U.S. Cities. Issue 11 (10th September 2021) - Jang, Hee Soun; Shi, Yu; Keyes, Laura; Dicke, Lisa A.; Kim, Jintak
ABSTRACT: This research examines the crisis management approaches of local governments in responding to the service demands of their homeless populations during the COVID-19 pandemic. The pandemic has generated challenges for cities in serving the homeless who often lack access to health care and may reside in outdoor camps or congregate shelters where the virus may spread. A review of the websites in 20 major U.S. cities shows that they are adopting a number of diverse and innovative crisis management strategies to mitigate the effects of the COVID-19 pandemic for their most vulnerable population. Information useful to practitioners and scholars is presented.